(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The current study comprised students from the Colleges of Education in Ghana, specifically those in their second and third years. The study period extended from January 2023 to October 2024. Two evaluations were conducted during the study period. In the initial evaluation, 425 year 1 students from 35 schools were assessed. In 2022, students in year 1 who participated in the initial assessment were involved upon their promotion to year 2. Students who took part in the classroom experiment were included. In the end, this approach produced a sample size of 631 second- and third-year students. Structured questionnaires were used for data collection, and the snowball sampling technique was applied to recruit participants. Structural equation modelling (SEM) is the analytical method used for data analysis. This approach is reliable for revealing the direct and indirect effects of the dependent and independent variables by clarifying their unique relationship. The results of the current study showed a positive correlation between students’ academic performance and grit and a growth mindset. In order to have a positive impact on academic achievement, grit should be measured by the persistence of effort rather than the constancy of interest and conscientiousness. Understanding how grit improves academic performance is linked to goal commitment and a growth mindset. According to the findings, students’ academic endeavours will be positively impacted by their perseverance, which is necessary to activate their growth mindset and commitment to goals.